The Utilization of Restorative Justice as a Means of Solving Crimes on the Outermost, Frontier and Remote Islands - Toffy, Giovani Babtista Montini; Nirahua, Salmon Eliazer Marthen; Toule, Elsa Rina Maya (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The legal community needs a criminal justice system that is fast, easy, economical and not complicated for the community of Letti Island District, which is the most remote outermost island, the court that hears criminal and civil cases is located on the Tanimbar Islands, the use of restorative justice by the Serwaru Police and the application of culture "Snyoli – Lieta” As “Hidup Orang Basudara” on the island in Letti Island acts as a filter in resolving criminal cases.Purposes of the Research: Analyze and discuss the basis for using restorative justice as a means of resolving criminal acts in the Serwaru Police Legal Area, Letti Island District, Southwest Maluku Regency as the outermost, foremost, and remote island.Methods of the Research: This research was conducted using an empirical legal research type. The empirical legal research method is a study of how the law is carried out in the field as it should be in people's lives.Results Main Findings of the Research: The basis for the use of justice restorative as a means of resolving criminal acts in the Legal Area of the Serwaru Police, Letti Island District, Southwest Maluku Regency as the outermost, foremost, remote island is based on the "Snyoli Lyeta" culture whose resolution mechanism is the same as the mediation process adopted inrestorative justice which prioritizes the deliberation process between victims and perpetrators of criminal acts, so that almost all criminal acts handled by the Serwaru Police in implementing National Police Chief Regulation Number 8 of 2021 can be resolved using justice.